Accounting for Carbon Stocks in Soils and Measuring GHGs Emission Fluxes from Soils: Do We Have the Necessary Standards? - Bispo, Antonio; Andersen, Lizzi; Angers, Denis A.; Bernoux, Martial; Brossard, Michel; Cécillon, Lauric; Comans, Rob N. J.; Harmsen, Joop; Jonassen, Knut; Lamé, Frank; Lhuillery, Caroline; Maly, Stanislav; et al. (Frontiers in Environmental Science, 2017)
Soil is a key compartment for climate regulation as a source of greenhouse gases (GHGs) emissions and as a sink of carbon. Thus, soil carbon sequestration strategies should be considered alongside reduction strategies for other greenhouse gas emissions. Taking this into account, several international and European policies on climate change are now acknowledging the importance of soils, which means that proper, comparable and reliable information is needed to report on carbon stocks and GHGs emissions from soil. It also implies a need for consensus on the adoption and verification of mitigation options that soil can provide. Where consensus is a key aspect, formal standards and guidelines come into play. This paper describes the existing ISO soil quality standards that can be used in this context, and calls for new ones to be developed through (international) collaboration. Available standards cover the relevant basic soil parameters including carbon and nitrogen content but do not yet consider the dynamics of those elements. Such methods have to be developed together with guidelines consistent with the scale to be investigated and the specific use of the collected data. We argue that this standardization strategy will improve the reliability of the reporting procedures and results of the different climate models that rely on soil quality data.